Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Bagian Produksi Genteng PT. KS Bangunan Leuwihalang Tasikmalaya - Nurhalimatu Syaidah; Mila Karmila; Barin Barlian (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the influence of training and work environment on employee performance in the roof tile production department at PT. KS Bangunan Leuwihaalang Tasikmalaya. The research method used is a survey with primary data collection through questionnaires filled out by respondents who are employees in the roof tile production department. The collected data was analyzed using multiple regression analysis techniques. The results of the study show that training has a positive and significant influence on employee performance in the roof tile production department. This indicates that the training provided to employees can enhance their skills in carrying out their tasks and responsibilities. Additionally, the work environment also has a positive and significant influence on employee performance. A conducive work environment, including factors such as coworker support, good communication, and adequate facilities, can provide motivation and improve employee performance. This study provides recommendations to the management of PT. KS Bangunan Leuwihaalang Tasikmalaya to enhance the effectiveness of training provided to employees in the roof tile production department. Additionally, attention should be given to efforts to improve and maintain a conducive work environment, enabling employees to work well and contribute optimally to the company's performance.